Botswana : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2007)
The Report on the Observance of Standards and Codes (ROSC)-Data Module provides an assessment of Botswana's macroeconomic statistics against the recommendations of the General Data Dissemination System, complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework, July 2003. It reveals that there has been a strengthening of the relevance of the data, the transparency of statistical policies and practices, and the accessibility of data and metadata. Staff of statistical agencies also exhibits a high level of professionalism and ethical standards.